2019
DOI: 10.1002/etc.4378
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Engineered Nanoparticle Surface Physicochemistry Revealed by Investigation of Changes in Copper Bioavailability During Sorption to Nanoparticles in the Aqueous Phase

Abstract: Sorption of chemical substances to nanoparticles (NPs) in the aqueous phase strongly influences NP physicochemisty, and investigations of these complex interactions can provide important insights into the environmental fate of NPs. The objective of the present study was to use differences in copper (Cu) bioavailability to investigate aqueous‐phase sorption with NPs that had different physicochemical characteristics (silicon [Si], perovskite, and titanium dioxide NPs [TiO2 NPs]). Sorption of Cu with NPs was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Irradiated ANT + TiO 2 –NP exposures showed significantly increased cyp 1 a and ephx 2 expression at 4 hpe compared to non-irradiated ANT + TiO 2 –NP exposures (Figure ). Several studies have confirmed that the presence of TiO 2 –NPs enhances ANT photodegradation and results in the production of bioavailable OPAH and OHPAH photoproducts, which is probably responsible for the observed induction of ephx 2 expression in the current study’s irradiated ANT exposures. , Results suggest that initially, photoproducts formed and quickly degraded, but the continued formation caused photoproduct accumulation, thus ensuing biotransformation. , The reduced expression of cyp 1 a (responsible for PPAH metabolism) in non-irradiated ANT + TiO 2 –NP exposures compared to exposures of ANT alone might indicate that ANT was not bioavailable and adsorption to the TiO 2 –NP surface may have occurred, which is consistent with previous studies (Figure S2C; 10, 18). These data further support photocatalytic capabilities of TiO 2 –NPs, considering that ephx 2 (responsible for encoding enzymes that metabolize OPAHs) were further induced in irradiated ANT + TiO 2 –NP exposures compared to exposures of ANT alone (Figure S2A).…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…Irradiated ANT + TiO 2 –NP exposures showed significantly increased cyp 1 a and ephx 2 expression at 4 hpe compared to non-irradiated ANT + TiO 2 –NP exposures (Figure ). Several studies have confirmed that the presence of TiO 2 –NPs enhances ANT photodegradation and results in the production of bioavailable OPAH and OHPAH photoproducts, which is probably responsible for the observed induction of ephx 2 expression in the current study’s irradiated ANT exposures. , Results suggest that initially, photoproducts formed and quickly degraded, but the continued formation caused photoproduct accumulation, thus ensuing biotransformation. , The reduced expression of cyp 1 a (responsible for PPAH metabolism) in non-irradiated ANT + TiO 2 –NP exposures compared to exposures of ANT alone might indicate that ANT was not bioavailable and adsorption to the TiO 2 –NP surface may have occurred, which is consistent with previous studies (Figure S2C; 10, 18). These data further support photocatalytic capabilities of TiO 2 –NPs, considering that ephx 2 (responsible for encoding enzymes that metabolize OPAHs) were further induced in irradiated ANT + TiO 2 –NP exposures compared to exposures of ANT alone (Figure S2A).…”
Section: Resultssupporting
confidence: 69%
“…GC–MS analyses for OPAHs and OHPAHs were performed using an Agilent 7890B GC system coupled to an Agilent 5977A mass spectrometer (MS) detector with electron impact ionization. OPAH and OHPAHs were analyzed with optimized methods previously published. ,,, All analyses were run in the selected ion monitoring mode. GC–MS analyses for all analytes were performed in triplicate using an Agilent DB-5MS (30 m × 0.25 mm I.D.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations